Application of photocatalysis for the treatment of grey water - Birben, Nazmiye Cemre. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2012., 2012)
Defined as the all wastewater coming from urban areas except any input from toilets, grey waters constitute the largest fraction of the total domestic wastewater consumption which may fluctuate in quality and quantity diversely. Since grey water is less contaminated by nutrients, inorganics and hazardous organic substances, it is a potential ‘’non-conventional’’ water resource. As a consequence, several treatment technologies to treat and reuse grey water have been studied widely. As one of these processes, photocatalytic oxidation, which relies upon the generation of highly reactive hydroxyl radicals under UV radiation, has become an innovative and effective technology for the treatment of grey water in terms of degradation of refractory organic matter and potential disinfection mechanism. This study aimed to investigate applicability of photocatalytic oxidation process to treat grey water sources. In this manner, synthetically prepared grey water samples were subjected to photocatalytic oxidation in the presence of TiO2 as the semiconductor photocatalyst. Further assessment of the system performance was observed by making compositional alterations of grey water samples in terms of organic matter loading, anion concentration, and microbiological content particularly. The results of photocatalytic oxidation experiments were deliberated by the determination of selected specified and specific UV-vis and fluorescence parameters. In addition to specified UV-vis parameters, DOC and bacterial content of samples were also evaluated in terms of removal efficiencies and photocatalytic degradation kinetics expressed by pseudo- first order kinetic modeling. As a consequence, photocatalytic oxidation of low load grey water with microorganism and low anion content revealed the most effective results in terms of the removal of selected parameters whereas lowest removal efficiencies for the selected parameters were achieved by photocatalytic oxidation of high load grey water with high anion content indicating the impact of organic matter loading and anion strength on the performance of photocatalytic oxidation process.
Keywords: Graywater (Domestic wastewater)